High-Density Genetic Map Construction and Stem Total Polysaccharide Content-Related QTL Exploration for Chinese Endemic Dendrobium (Orchidaceae) - Lu, Jiangjie; Liu, Yuyang; Xu, Jing; Mei, Ziwei; Shi, Yujun; Liu, Pengli; He, Jianbo; Wang, Xiaotong; Meng, Yijun; Feng, Shangguo; Shen, Chenjia; Wang, Huizhong (Frontiers in Plant Science, 2018)
Plants of the Dendrobium genus are orchids with not only ornamental value but also high medicinal value. To understand the genetic basis of variations in active ingredients of the stem total polysaccharide contents (STPCs) among different Dendrobium species, it is of paramount importance to understand the mechanism of STPC formation and identify genes affecting its process at the whole genome level. Here, we report the first high-density single-nucleotide polymorphism (SNP) integrated genetic map with a good genome coverage of Dendrobium. The specific-locus amplified fragment sequencing (SLAF-seq) technology led to identification of 7,013,400 SNPs from 1,503,626 high-quality SLAF markers from two parents (D. moniliforme ♀ × D. officinale ♂) and their interspecific F1 hybrid population. The final genetic map contained 8, 573 SLAF markers, covering 19 linkage groups (LGs). This genetic map spanned a length of 2,737.49 cM, where the average distance between markers is 0.32 cM. In total, 5 quantitative trait loci (QTL) related to STPC were identified, 3 of which have candidate genes within the confidence intervals of these stable QTLs based on the D. officinale genome sequence. This study will build a foundation up for the mapping of other medicinal-related traits and provide an important reference for the molecular breeding of these Chinese herb.